DEVELOPMENT OF STUDENT ENTREPRENEURIAL COMPETENCIES THROUGH INDEPENDENT ENTREPRENEURSHIP IN INDONESIA - Suranto, Suranto; Munajat Tri Nugroho; Kussudyarsana, Kussudyarsana; Muhtadi, Muhtadi; Moh fahmi Johan Syah; Nurhidayat, Nurhidayat; Soepatini, Soepatini; Aan Sofyan; Fari Adi Prasetya (SEAN Institute, 2023)
Research on a goodness of fit model for developing students' entrepreneurial competencies through the independent entrepreneurship program. The resulting benefits of the independent entrepreneurship learning model are able to increase the mental competence of business independence. Data collection through observation, questionnaires, interviews, field practice, documentation and literature study. Research object of independent entrepreneurial students from implementing universities at Muhammadiyah University, Surakarta. Data analysis methods using validity, reliability, confirmatory analysis tests, t-student tests by looking at the differences before and after getting the independent entrepreneurship learning model. Development research uses one shot case study experiments, quantitative and qualitative approaches. Students receive guidance, mentoring, counseling, empowerment and training in entrepreneurial activities. Research design through one shot case study, through workshop stages, internships in MSMEs, product design and marketing. Novelty research, the independent entrepreneurship learning model through MBKM is implemented in Indonesia which involves MSMEs mentors, MSMEs interns, competent assistants in the business sector, field supervisors, students from various parts of Indonesia, state universities and private universities who take part in the WMK program. Based on the results, it is concluded that the development of a model for increasing entrepreneurial competence is declared a goodness of fit model, meaning that the model is very feasible in increasing the mental competence of business independence. The trend in the development of entrepreneurial mental competence has increased (increased) after receiving the independent entrepreneurial model treatment. Based on the t-test, there are differences in students' entrepreneurial mental competence before and after gaining independent entrepreneurial competence.